Applying tenets of code of the street to intimate partner violence perpetration and victimization - Zavala, Egbert (Journal of crime and justice, 2025)
While studies testing ‘code of the street’ have generally supported a relationship between it and various forms of violent and non-violent behaviors, including victimization, the theory has not been applied to explain intimate partner violence (IPV) perpetration and victimization among college students. Recently, scholars have maintained that the code of the street may extend beyond the inner cities and may be applicable in explaining violent behavior by college students. Therefore, the main research question addressed in this study is how applicable, if at all, is tenets of code of the street in explaining intimate partner IPV perpetration and victimization among college students. Using a United States subsample of 4,162 college students contained in the cross-sectional International Dating Violence Study, results from logistic regression models showed that the tenets of code of the street is associated with IPV perpetration and victimization. More importantly, code of the street remains statistically significant even after controlling for well-documented risk markers of IPV. Implications of our findings suggest that intervention and prevention programs aimed at altering code of the street beliefs should reduce IPV perpetration and victimization. Further results, as well as the study’s limitations, are discussed.